Insect infestation during sporadic flowering of Dendrocalamus hamiltonii in Meghalaya, India - Sasanka Sekhar Ghosh; Selim Mehmud (Advances in Bamboo Science)
This study recorded occurrences of the sap sucking insects Antonina pretiosa and Planococcus citri on the inflorescence of Dendrocalamus hamiltonii during its sporadic flowering during the month of May and June, 2024 in Ri-Bhoi district of Meghalaya. The inflorescences where the insects occurred failed to form viable seeds.